Case Report of a Child after Hematopoietic Cell Transplantation with Acute Aspergillus Tracheobronchitis as a Cause for Respiratory Failure - Stefanie Gauguet; Kate Madden; Jennifer Wu; Christine Duncan; Gi Soo Lee; Tonya Miller; William C. Klingensmith; Sandra K. Burchett; Meredith van der Velden (Case Reports in Pediatrics)
Rapid respiratory failure due to invasive mycosis of the airways is an uncommon presentation of Aspergillus infection, even in immunocompromised patients, and very few pediatric cases have been reported. Patients with Aspergillus tracheobronchitis present with nonspecific symptoms, and radiologic studies are often noninformative, leading to a delay in diagnosis. Prompt initiation of adequate antifungal therapies is of utmost importance to improve outcome. We report the case of a 9-year-old girl with chronic myelogenous leukemia who developed respiratory distress 41 days after hematopoietic cell transplantation and rapidly deteriorated despite multiple interventions and treatment modalities.